Blue and Green Cities The Role of Blue-Green Infrastructure in Managing Urban Water Resources - Brears, Robert C. (Palgrave Macmillan UK, 2018)
This book offers new research on urban policy innovations that promote the application of blue-green infrastructure in managing water resources sustainably. The author argues that urban water managers have traditionally relied on grey infrastructural solutions to mitigate risks with numerous economic and environmental consequences. Brears explores the role urban water managers have in implementing blue-green infrastructure to reduce ecological damage and mitigate risk. The case studies in this book illustrate how cities, of differing climates, lifestyles and income-levels, have implemented policy innovations that promote the application of blue-green infrastructure in managing water, wastewater and stormwater sustainably to reduce environmental degradation and enhance resilience to climate change. This new research on urban policy innovations that promote the application of blue-green infrastructure in managing water resources sustainably will be of interest to those working on water conservation and policy. Robert C. Brears is the founder of Mitidaption, Mark and Focus, and is Director on the International Board of the Indo Global Chamber of Commerce, Industries and Agriculture. He is the author of Urban Water Security (2016).